(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Bisphenol A, one of the environmental endocrine disrupting chemicals, was shown to have a weak estrogen activity and could disrupt thyroid function to some degree. Iodine, which is the most essential microelement that is used for the synthesis of thyroid hormones in humans, was proven to give rise to thyroid diseases, such as thyroiditis, thyroid nodular goiter, and so on. There are relatively very few studies that have considered the role that both Iodine and Bisphenol A play in the development of papillary thyroid carcinoma. Therefore, this crosssectional observational study was carried out to explore the relationship between Iodine, Bisphenol A and Papillary Thyroid Carcinoma. The study included 113 subjects aged from 20 years to 80 years selected from Qilu Hospital of Shandong University from February 2015 to September 2015 and 65 healthy volunteers residing in Jinan, P.R. China. We compared the differences of the concentrations of Urinary Iodine, Urinary Bisphenol A and Serum Bisphenol A among patients of Papillary Thyroid Carcinoma, nodular goiter and normal population. In the PTC and nodular goiter group, urinary BPA and Iodine concentrations were significantly higher than controls stating that the excretion of Iodine and BPA were increased. Meanwhile 23 patients with papillary thyroid carcinoma (43%) had excessive iodine nutrition compared to only 6 volunteers with excessive iodine intake in the control group (9%). These findings suggest that excessive dietary iodine intake is a risk factor for thyroid cancer. Moreover, the significant association between urinary creatine-adjusted BPA and iodine suggest that they might have a synergistic effect on the thyroid. JCMCTA 2016 ; 27 (2) : 50 - 59